Efeito das diferentes direções de aplicação de jato de fluido de corte no torneamento de um aço de difícil usinagem - Bertoncini, Alexandre Ricardo Alferes [UNESP] (2007)
In this work it was studied the behavior of the turning operation of ISO 683-XV-8, a difficult to machine steel, using coated sintered carbide insert, under high pressure application of the cutting fluid in the three main heat generating areas: interface chip-tool; primary zone of shear, and area of tool-workpiece contact. For that, a system of cutting fluid application of jes under high-speed and high-pressure, that can be applied in an individual and simultaneous way was designed and mounted in a conventional lathe. The system consists of a low cost piston pump, a control system of the flow and pressure of the fluid flow and a device capable to control the variation of the jets application angles. The objective was to improve the performance of the high-pressure jets, in each application position, controlling the positions and the angles of application of the fluid. The performance of each application position of the jets was measured, in terms of tool life, cutting force components, relative temperature of the tool, tool wear and workpiece surface roughness, as well as the analysis of the shape of the generated chips. In general, the results show that individual applications with high pressure jet directed on to chip-tool interface presented the best results, followed by the jet pointed to the work piece-tool and work piece-chip. The tool life increased 152% when compared with the conventional fluid application. With simultaneous jets it was verified that a larger synergy exists between the ship-tool jets and workpiece-tool jets than between the chip-tool jets and workpiece-ship jets.